Live Microalgae-Based Diets as Enrichment to Improve the Nutritional Profile of the Calanoid Copepod Acartia tonsa (Dana, 1849) Nauplii - Martino, Andrea; Montero Vítores, Daniel; Roo Filgueira, Francisco Javier; Holt, William Vicent; Lavorano, Silvia; Narizzano, Riccardo; Otero Ferrer, Francisco (Aquaculture Research, 2023)
Most emerging species in marine aquaculture and the aquarium industry have a sensitive and small-mouthed larval stage, and their culture is very challenging due to a lack of appropriate early feeding protocols. The use of copepods has been widely recognized as a good alternative to traditional fish live feeds (rotifers and Artemia spp.), especially for new species targeted for the multibillion-dollar marine aquarium trade. However, most copepod culture trials are focused on biomass production, while their nutritional requirements and enrichment protocols remain scarcely known. The main objective of this study was to determine the dietary contribution of three microalgae-based diets, provided as a mono R (Rhodomonas salina) or binary I–R (Isochrysis galbana + R. salina) and T–R (Tetraselmis suecica + R. salina), on the biochemical composition (proximate and fatty acids (FAs)) and survival of the calanoid copepod Acartia tonsa (nauplii) versus the conventional rotifer Brachionus plicatilis throughout 96 hr exposure. Both live preys were characterized by the highest protein and total n-3 long-chain polyunsaturated FAs (LC-PUFAs) content when fed with the binary diet I–R compared to other treatments, although the nutritional value of A. tonsa nauplii was always much higher compared to B. plicatilis. In general, there was a wide difference in proximate and FAs composition between the two preys, denoting A. tonsa as better live feed in terms of capacity to retain n-3 LC-PUFAs, especially eicosapentanoic acid (20 : 5n-3) and docosahexanoic acid (22 : 6n-3). The present study highlights the nutritional profile of enriched A. tonsa nauplii and contributes to the production of high-quality live feeds, which may be able to reach the nutritional needs of new marine fish species during their larval development, as well as contributing to the improvement of A. tonsa culture. 0,54 2,184 Q2 Q3 SCIE 11,0